2021
DOI: 10.7150/ijbs.58163
|View full text |Cite
|
Sign up to set email alerts
|

MiR-124 Negatively Regulated PARP1 to Alleviate Renal Ischemia-reperfusion Injury by Inhibiting TNFα/RIP1/RIP3 Pathway

Abstract: Renal ischemia-reperfusion injury (IRI) is one of the underlying causes of acute kidney injury and also an unavoidable problem in renal transplantation. Lots of miRNAs and targets have been found to participate in some post-transcriptional processes in renal IRI, however, the detailed knowledge of miRNA targets and mechanism is unknown. In this study, miR-124 was found inhibited and PARP1 was overexpressed in renal IRI cells and mouse models. Dual-luciferase reporter assay revealed that miR-124 post-transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…As we previously reported that ADAMTS7 was upregulated after H 2 O 2 and proinflammatory cytokine stimuli, 32 ADAMTS7 upregulation in both models was possibly due to oxidative stress and inflammatory response, which mediated the pathogenesis of SLE and renal I/R injury. [33][34][35][36][37] Moreover, we demonstrated that ADAMTS7 deficiency rescued CFH degradation and alleviated complement-mediated renal pathologies, but without affecting complement-dependent serum bactericidal activity. Therefore, ADAMTS7, which degrades CFH, would be a promising anticomplement therapeutic target for related renal injuries, potentially reducing the risk of infection.…”
Section: Discussionmentioning
confidence: 78%
“…As we previously reported that ADAMTS7 was upregulated after H 2 O 2 and proinflammatory cytokine stimuli, 32 ADAMTS7 upregulation in both models was possibly due to oxidative stress and inflammatory response, which mediated the pathogenesis of SLE and renal I/R injury. [33][34][35][36][37] Moreover, we demonstrated that ADAMTS7 deficiency rescued CFH degradation and alleviated complement-mediated renal pathologies, but without affecting complement-dependent serum bactericidal activity. Therefore, ADAMTS7, which degrades CFH, would be a promising anticomplement therapeutic target for related renal injuries, potentially reducing the risk of infection.…”
Section: Discussionmentioning
confidence: 78%
“…[ 72 ] Recently, miR-124 was found to attenuate renal IRI by negatively regulating PARP1 through inhibiting the TNFα/RIP1/RIP3 pathway and rescued the miR-124. [ 73 ] MiR-26a-5p alleviated apoptosis by inhibiting the expression of RIP1, RIP3, and MLKL in necrotizing apoptosis. [ 74 ]…”
Section: Microrna Crosstalk With Pcd In Renal Diseases and Clinical A...mentioning
confidence: 99%
“…TNF-α has been reported to bind to the TNF receptor 1 on the surface of TECs to induce RIP3-dependent necrotizing apoptosis ( 70 , 71 ). In I/R-induced AKI, TNFα has also been reported to exacerbate kidney injury through the receptor-interacting protein 3(RIP1)/RIP3 necroptosis signaling pathway ( 72 ). Type I interferon α (IFN-α) is a multifunctional active cytokine that induces apoptosis in renal TECs through activation of caspase-3, caspase-8, and caspase-9, leading to DNA fragmentation and nuclear condensation ( 73 ).…”
Section: Immune Cells Promote Various Types Of Programmed Cell Deaths...mentioning
confidence: 99%